ANALISIS KETELITIAN HORIZONTAL ORTHOREKTIFIKASI CITRA PLEIADES UNTUK PEMBUATAN PETA DASAR RDTR PESISIR (Studi Kasus : Kecamatan Semampir, Kota Surabaya) - Sukojo, Bangun Muljo; Hidayat, Husnul; Santoso, Romario (GEOID, 2017)
The quality of accuracy and precision was the main problem in survey and mapping. One of the problems these there were in remote sensing, namely in the geometric correction is orthorectification on the satellite image. Products from orthorectification is needed in the manufacture of large-scale maps of 1: 5000 as for the purpose of detailed spatial plan map. The data used for the orthorectification process is a high resolution image of the Pleiades, a Ground Control Point and DEM Alos PALSAR. DEM used as elevation data to correct or eliminate the influence of relief displacement of image data due to variations in the earth's surface terrain. In this study, using seven of ground control points spread evenly on the location of the research, which is in District Semampir, Surabaya. The ground control points obtained through direct measurements in the field with GPS Geodetic using static methods. Orthorectification method using Rigorous. The results of this study indicate CE90 and LE90 values using the Rigorious methods, geometric precision can be seen from the CE90 and LE90 where the smaller the value, the result of more thorough and accurate image. For eligibility image, obtained by multiplying the value of the coefficient RMSE and thoroughness in which the image of the Pleiades 1 qualifies a map scale of 1: 5000.